Analysis of foreign experience in involving women in science - Kangalakova, D.; Аbzhan Zh.; Satpayeva, Z.; Ibraimova, S. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of this article is to analyze foreign experience in supporting women scientists in order to develop recommendations for Kazakhstan. Methods: This article used an integrated approach to the choice of methodology. The research methods were generally scientific, these are dialectics, a systematic approach, methods of analysis and synthesis, typology, generalization and refinement. That is, the methodology section includes a set of methods used to analyze the state of women scientists in the world based on foreign documents. Results: During the study, indicators of the share of female scientists among the total number of scientists in the countries of the world were studied. It was found that in the post — Soviet countries the proportion of women scientists is more than 50 %, in developed countries the proportion of women scientists is relatively low. Here, firstly, we can see a large number of scientists in developed countries, and secondly, we can see a large number of foreign women scientists. And the situation in Kazakhstan and the CIS states is the opposite. In addition, programs to support women scientists in the leading countries of the world were discussed. Conclusions: In conclusion, the opportunities and rights of women scientists abroad are wider than those of domestic scientists. the potential of domestic women scientists is not revealed in the development of the country’s economy. In this regard, directions were proposed to support women scientists in Kazakhstan. The theoretical value of this article is to fill the theory in the problem of studying the empowerment of female scientists. The practical significance of this study is the proposed provisions that can be checked by public administration bodies.